Human umbilical cord-derived mesenchymal stem cells alleviate valproate-induced immune stress and social deficiency in rats - Sun, Shixiong; Luo, Shilin; Chen, Jie; Zhang, Ou; Wu, Qiongying; Zeng, Nianju; Bi, Jinlian; Zheng, Chunbing; Yan, Tenglong; Li, Zhiyuan; Chen, Jindong; Zhang, Yilei; et al. (Frontiers in Psychiatry, 2024)
Autism spectrum disorders (ASD) are a set of heterogeneous neurodevelopmental diseases characterized by impaired social interactions and stereotypic behaviors. Current clinical care is palliative at the most and there remains huge unmet medical need to fully address the core symptoms of ASD. Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) are emerging as a promising candidate for ASD treatment, but the precise mechanism remains controversial. In the present study, we determined the therapeutic effects of intravenous administration of hUC-MSCs in rats challenged with valproic acid (VPA) during gestation, a well-defined rat model of autism. We found that hUC-MSCs significantly alleviated microglial activation in the brain especially anterior cingulate cortex and effectively improved the sociability of the rats. In vitro studies also showed that hUC-MSCs promoted the growth of primarycultured cortical neurons. Our study has demonstrated a strong anti-inflammatory and cognition-promoting effects which prime hUC-MSCs as an excellent alternative resource for the treatment of ASD.